Gambaran Tingkat Pengetahuan Wanita Usia Subur Tentang HIV/AIDS di Wilayah Kerja Puskesmas Gurah Kabupaten Kediri - Ratna Frenty Nurkhalim (Masokan: Ilmu Sosial dan Pendidikan, 2021)
HIV / AIDS is an infectious disease caused by infection with the Human Immunodeficiency Virus (HIV) which attacks the immune system. (RI Ministry of Health, 2017). The high case of HIV / AIDS in women is feared to have an impact on the increase in cases of HIV / AIDS in children who get from perinatal transmission or transmission of infections that occur during pregnancy or childbirth. Another contributing factor is the lack of knowledge and awareness about HIV / AIDS that has threatened ordinary people including women of childbearing age. This study aims to determine the level of knowledge of women of childbearing age about HIV / AIDS in the Gurah Health Center area of ​​Kediri Regency. The method used was cross-sectional by distributing questionnaires to a group of women of childbearing age with a total sample of 98 respondents. With variables including the characteristics of respondents and knowledge of HIV / AIDS. Based on the research results obtained for the most age at the end of adulthood (35.7%), the most education was high school / vocational school (62.2%), IRT work (65.3%), electronic media information sources (41.8%). While knowledge of HIV / AIDS was sufficient as much as 43.9%, knowledge about transmission is low (49.9%), knowledge of prevention about limiting sexual relations (70.4%), condom use (55.1%), knowledge of signs and symptoms of people appear healthy (73.5%) , knowledge of characteristics affected by HIV / AIDS (59.2%), knowledge of prevention of HIV / AIDS testing (54.1%), and place of testing services (53.1%). The conclusion that can be taken was the level of knowledge of women of childbearing age about HIV / AIDS was in the sufficient category and was expected to be further improved so that it becomes a high level by conducting counseling by health workers in the Puskesmas and other agencies.   HIV/AIDS merupakan penyakit menular yang disebabkan oleh infeksi Human Immunodeficiency Virus (HIV) yang menyerang sistem kekebalan tubuh. (Kemenkes RI, 2017). Tingginya kasus HIV/AIDS pada perempuan dikhawatirkan akan ikut berdampak pada peningkatan kasus HIV/AIDS pada anak-anak yang didapat dari penularan melalui perinatal atau penularan infeksi yang terjadi pada saat kehamilan atau persalinan. Faktor penyebab lainnya adalah kurangnya pengetahuan dan kesadaran tentang HIV/AIDS yang telah mengancam kalangan orang biasa termasuk wanita usia subur. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan wanita usia subur tentang HIV/AIDS di wilayah Puskesmas Gurah Kabupaten Kediri. Metode yang digunakan adalah cross-sectional dengan menyebarkan kuesioner ke kelompok wanita usia subur dengan jumlah sampel sebanyak 98 responden. Dengan variabel meliputi karakteristik responden dan pengetahuan HIV/AIDS. Berdasarkan penelitian diperoleh hasil untuk usia terbanyak pada dewasa akhir (35.7%), pendidikan terbanyak yaitu SMA/SMK (62.2%), pekerjaan IRT (65.3%), sumber informasi media elektronik ( 41.8%). Sedangkan pengetahuan HIV/AIDS yaitu cukup sebanyak 43.9%, pengetahuan mengenai penularan yaitu rendah (49.9%), pengetahuan pencegahan tentang membatasi hubungan seksual (70.4%), pemakaian kondom (55.1%), pengetahuan tanda dan gejala orang tampak sehat (73.5%), pengetahuan ciri terkena HIV/AIDS (59.2%), pengetahuan penanggulangan adanya tes HIV/AIDS (54.1%), dan tempat pelayanan tes (53.1%). Simpulan yang dapat diambil adalah tingkat pengetahuan wanita usia subur tentang HIV/AIDS berada pada kategori cukup dan diharapkan dapat lebih ditingkatkan sehingga menjadi tingkatan yang tinggi dengan dilakukan penyuluhan oleh tenaga kesehatan yang ada di Puskesmas maupun instansi lainnya.